Pemodelan dan Simulasi Shunt Active Power Filter (SAPF) Menggunakan Metode PI-GWO pada Sistem Tenaga Listrik IEEE 14 Bus - Achmad Rifa’i; 081347087013 Aprillia; Yun Tonce Kusuma Priyanto (Specta, 2023)
Current technological developments generally use sophisticated equipment which is categorized as a non-linear load. The massive use of non-linear loads causes side effects on the quality of electric power. Electric power systems that are connected to non-linear loads will experience distortion in current and voltage by harmonics due to the engineering of voltage waveforms due to the installation of many converters operating at frequencies that do not match the utility frequency of 50 or 60 Hz. Taking into account the great benefits for humans, the use of non-linear loads cannot be reduced but can be applied by keeping non-linear loads operating with good quality electric power. Therefore, harmonic filter equipment is needed to reduce harmonics. Passive filters and active filters can be used where active filters have many advantages compared to passive filters because they can adjust to varying working frequencies. To obtain more optimal harmonic reduction results, an active filter Shunt Active Power Filter (SAPF) using a PI controller tuned with the Gray Wolf Optimizer (GWO) optimization method is designed. The SAPF PI-PSO method is used as a comparison. The SAPF experiment on the IEEE 14 bus test system, PSO obtained better ITAE error results and computation time than GWO. The ITAE value and PSO computing time were 108.5821 second and 4255.097192 second, respectively, while GWO obtained 109.0172 second and 4379.461 second. However, the GWO-tuned SAPF is more able to reduce the THD of the 12 bus current on the IEEE 14 bus system by 13%.